Zonisamide as an Adjunctive Treatment to Cognitive Processing Therapy for Veterans With Posttraumatic Stress Disorder and Comorbid Alcohol Use Disorder: A Pilot Study. Issue 6 (27th May 2020) - Petrakis, Ismene; Ralevski, Elizabeth; Arias, Albert J.; DeNegre, Diana; Newcomb, Jenelle; Gianoli, Mayumi; McCarthy, Elissa; Meshberg‐Cohen, Sarah; Yoon, Gihyun
Abstract : Background and Objectives: There are high rates of comorbid alcohol use disorder (AUD) among those who have posttraumatic stress disorder (PTSD). Ideally, treatment for comorbidity should address both disorders simultaneously. Zonisamide, an anticonvulsant, may be effective in decreasing alcohol use and may attenuate symptoms of PTSD. Treatment strategies can include medication in combination with a proven evidence‐based psychotherapy designed to treat PTSD, such as cognitive processing therapy (CPT). Methods: This 12‐week pilot study was designed to test feasibility, acceptability, and preliminary efficacy of zonisamide (400 mg) as an adjunct to CPT for veterans with PTSD and comorbid AUD. Veterans ( n = 24) with PTSD and current alcohol dependence were randomized in a 3:1 ratio to receive zonisamide or placebo in a double‐blind fashion. All subjects received CPT enhanced to include sessions addressing drinking behavior. Results: Subjects overall reported a significant decrease in drinking outcomes, craving, and symptoms of PTSD. Zonisamide was well‐tolerated and easily administered with CPT, which was also well‐tolerated. Exploratory analysis of comparison of groups suggests there was no advantage of zonisamide vs placebo in drinking or PTSD outcomes. There was a numeric but nonsignificant higher rate of abstinence with zonisamide (50%) vs placebo (33%). Conclusion and Scientific Significance: The interpretation of the results is limited by the pilot nature of this study. The combination of psychosocial treatment with medication management mimics real‐world treatment. In order to isolate the individual contributions of medication vs psychotherapy a much larger study would need to be conducted. (Am J Addict 2020;29:515–524)